2021
DOI: 10.3390/ijerph18073331
|View full text |Cite
|
Sign up to set email alerts
|

More Than Shelter: Housing for Urban Maternal and Infant Health

Abstract: Housing quality, stability, and affordability have a direct relationship to socioemotional and physical health. Both city planning and public health have long recognized the role of housing in health, but the complexity of this relationship in regard to infant and maternal health is less understood. Focusing on literature specifically relevant to U.S. metropolitan areas, I conduct a multidisciplinary literature review to understand the influence of housing factors and interventions that impact infant and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Policies guiding mortgage lending practices and community development shape communities, and more specifically, the resources, exposures, and social capital they contain. For instance, safe, stable, affordable, and quality housing has a direct relationship with physical and mental health, and is a key SDoH in health promotion [164]. Racial and ethnic minority families are more likely to live in areas with concentrated poverty, experience housing insecurity and housing segregation which contribute to greater disparities in infant mortality and birth outcomes [163][164][165].…”
Section: Societal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies guiding mortgage lending practices and community development shape communities, and more specifically, the resources, exposures, and social capital they contain. For instance, safe, stable, affordable, and quality housing has a direct relationship with physical and mental health, and is a key SDoH in health promotion [164]. Racial and ethnic minority families are more likely to live in areas with concentrated poverty, experience housing insecurity and housing segregation which contribute to greater disparities in infant mortality and birth outcomes [163][164][165].…”
Section: Societal Factorsmentioning
confidence: 99%
“…For instance, safe, stable, affordable, and quality housing has a direct relationship with physical and mental health, and is a key SDoH in health promotion [164]. Racial and ethnic minority families are more likely to live in areas with concentrated poverty, experience housing insecurity and housing segregation which contribute to greater disparities in infant mortality and birth outcomes [163][164][165]. One study comparing state-level measures of structural racism and Black infant mortality found that for all states, increasing racial inequity in unemployment was associated with a 5% increase in Black infant mortality [14].…”
Section: Societal Factorsmentioning
confidence: 99%
“…In an urban‐based quasi‐experimental study of over 10,000 participants, Pollack and colleagues reported that people living in unaffordable housing had increased odds of poor self‐rated health (AOR 1.75, 95% CI 1.33, 2.29) (Pollack et al, 2010). Reece brilliantly describes the pillars of influence of housing as a social determinant of maternal health (Reece, 2021). These primary pathways of housing conditions and habitability, neighbourhood effect, and housing stability/affordability are witnessed in these interviews and affect maternal health outcomes (Reece, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reece brilliantly describes the pillars of influence of housing as a social determinant of maternal health (Reece, 2021). These primary pathways of housing conditions and habitability, neighbourhood effect, and housing stability/affordability are witnessed in these interviews and affect maternal health outcomes (Reece, 2021). Systemic racism is undoubtedly a piece of this puzzle that we must address.…”
Section: Discussionmentioning
confidence: 99%
“…Unsafe, insecure and damp housing has well-established links to adverse socio-emotional and physical health outcomes ( Rolfe et al , 2020 ). For mothers/parents at such a vulnerable time, insecure and inadequate housing has multifaceted, complex and intergenerational effects on health ( Reece, 2021 ) and destabilizes their ability to adjust to new challenges of mother/parenthood. The idea that housing is linked to adverse health is not new, albeit unresolved and under-addressed; however, linking housing as a core strategy within a coordinated maternal health promotion approach crucially steps away from remaining at more widespread behavioural approaches to improving maternal health.…”
Section: Addressing Upstream Determinantsmentioning
confidence: 99%